2019
DOI: 10.1242/bio.042861
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of mRNA and following protein synthesis of CaMKIIα at the long-term potentiation-induced site

Abstract: Late-phase long-term potentiation (L-LTP) in hippocampus, thought to be the cellular basis of long-term memory, requires new protein synthesis. Neural activity enhances local protein synthesis in dendrites, which in turn mediates long-lasting synaptic plasticity. Ca 2+ /calmodulin-dependent protein kinase IIα (CaMKIIα) is a locally synthesized protein crucial for this plasticity, as L-LTP is impaired when its local synthesis is eliminated. However, the distribution of Camk2a mRNA during L-LTP induction remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Additionally, neurons host up to several thousand synapses where mRNA localisation and local translation are key for ensuring the rapid spatio-temporal regulation of protein synthesis required for synaptic plasticity [ 3 , 6 , 72 ]. For instance, Camk2ɑ mRNA was found to localise to dendrites at sites receiving high-frequency stimulation [ 73 ], whereas NMDA-induced neuronal activation was demonstrated to trigger the translocation of Calmodulin-3 mRNA into dendrites in rat cortical neurons [ 74 ]. Deep sequencing of hippocampal neuropil coupled with Nanostring analysis and high-resolution fluorescent in situ hybridisation, estimated the number of distally localised mRNAs in dendrites to be around 2500 [ 75 ].…”
Section: Neuronal Mrna Localisationmentioning
confidence: 99%
“…Additionally, neurons host up to several thousand synapses where mRNA localisation and local translation are key for ensuring the rapid spatio-temporal regulation of protein synthesis required for synaptic plasticity [ 3 , 6 , 72 ]. For instance, Camk2ɑ mRNA was found to localise to dendrites at sites receiving high-frequency stimulation [ 73 ], whereas NMDA-induced neuronal activation was demonstrated to trigger the translocation of Calmodulin-3 mRNA into dendrites in rat cortical neurons [ 74 ]. Deep sequencing of hippocampal neuropil coupled with Nanostring analysis and high-resolution fluorescent in situ hybridisation, estimated the number of distally localised mRNAs in dendrites to be around 2500 [ 75 ].…”
Section: Neuronal Mrna Localisationmentioning
confidence: 99%
“…Considering the relative abundance (with CaMKIIα being highly expressed compared to SLAMR), we speculated that SLAMR might play a role in mediating the activity of CaMKIIα in dendrites. Previous studies demonstrated that CaMKIIα is localized in dendrites and translocated to spines in response to neuronal activity 76 78 . Consistent with a role in modulating CaMKII activity, we observed that the loss of SLAMR function resulted in a reduction in the active pool of CaMKIIα (T282 phosphorylated) in synaptoneurosomes.…”
Section: Discussionmentioning
confidence: 99%